Study on Compaction Effect and Process of Reclaimed Soil of Nonmetallic Mines in Xinjiang, China - Kaikai Wang; Zizhao Zhang; Guobin Tang; Xiaodong Tan; Qianli Lv; Fengjun Shao; Xiaoping Li (Advances in Materials Science and Engineering)
Reclaimed soil is the key substrate for land reclamation and ecological restoration in the mine areas. The change of the density of reclaimed soil of the nonmetallic mines in Xinjiang during the land reclamation process was studied in this paper. Firstly, the in situ test method of static load was used to simulate the compaction of reclaimed soil with different thickness of overlying soil by different compaction times of mines reclamation machinery, and field in situ test compaction data were obtained. Then, the numerical simulation method was used to simulate the variation process of displacement and porosity at different depths for different thickness of the reclaimed soil under different compaction conditions. The numerical simulation and the in situ test results verified each other to acquire the compaction process and results of reclaimed soil under different compaction. The results showed that the numerical simulation results were consistent with the in situ test. The reclaimed soil thickness and compaction times were crucial factors affecting the compaction effect of the soil. The difference between the three times compaction and the uncompacted soil was obvious, and the effect of single compaction was weakened with the increase of compaction times. Under the same compaction action, the thicker the soil was, the less obvious the compaction effect would be. In the process of reclamation, the compaction effect of the surface part (at the depth of 10 cm) was visible, and the amount of compression and springback was larger. The research results can provide a reference to the land reclamation of nonmetallic mines in Xinjiang, China.